The Importance of Nature Exposure and Physical Activity for Psychological Health and Stress Perception: Evidence From the First Lockdown Period During the Coronavirus Pandemic 2020 in France and Germany - Javelle, Florian; Laborde, Sylvain; Hosang, Thomas Jean; Metcalfe, Alan James; Zimmer, Philipp (Frontiers in Psychology, 2021)
Objective: This cross-sectional questionnaire-based study aims to compare physical activity and nature exposure levels between people living in France and Germany during the lockdown. Furthermore, the secondary aim is to observe the relationship between perceived stress, psychological health, physical activity, and nature exposure in Germany and France during the COVID-19 related lockdown of April/May 2020. Methods: The study includes 419 participants that have completed the Perceived Stress Scale 10, the World Health Organization Quality of Life – BREF, the Godin-Shephard Leisure Time Physical Activity Questionnaire, the modified Nature Exposure Scale and complementary questions related to the lockdown period from April 19th to May 11th 2020. Multiple regression models were constructed to evaluate the relationship of nature exposure and physical exercise with overall stress perception and psychological health in France and Germany when considering a broad range of covariates. Results: Exposure to nature during the lockdown (ƞp²=.019, p<.001), amount of physical activity ƞp²=.026, p<.001), and psychological health ( ƞp2=.044 - p<.001) were greater in German compared with French participants. The stress and psychological health regression models both explained 9.9% of the results’ variance where both physical activity (Godin Index) and Nature Exposure total score were significant predictor. When including all significant covariates the models explained 30.7% for the perceived stress and 42.4% for the psychological health total overall variance. Conclusion: Physical activity and nature exposure are significant predictors of stress levels and psychological health. These non-pharmacological alternatives should be considered more systematically as potential treatment for stress and psychological disorders.